2020
DOI: 10.18844/cjes.v15i1.4557
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of high school students’ cognitive structures related to musical genre via word association test

Abstract: The aim of this study, via the Word Association Test, an alternative assessment and evaluation technique, to reveal the cognitive structures by determining high school students' perceptions about music genres. For this purpose, in the spring semester of 2015–2016 academic year, Data in the study is obtained with the participation of 100 students in 11th and 12th. Independent word association test was used to collect data. In order to create the test, music genres, namely, Turkish Folk Music, Turkish Art Music,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…It is explicit that teachers perceived this topic as a global issue since the COVID-19 pandemic has spread over whole countries after 2019, and the experiences of diverse nations were also typical. Only Sert (2021) reported that COVID-19 was a global issue that coincided with the current study findings under the infectious diseases category; however, the anti-vaccination topic under this category did not exist in any of the studies in the literature as a global issue.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is explicit that teachers perceived this topic as a global issue since the COVID-19 pandemic has spread over whole countries after 2019, and the experiences of diverse nations were also typical. Only Sert (2021) reported that COVID-19 was a global issue that coincided with the current study findings under the infectious diseases category; however, the anti-vaccination topic under this category did not exist in any of the studies in the literature as a global issue.…”
Section: Discussionsupporting
confidence: 75%
“…Reviewing the national literature (Artun & Özseygeç, 2020;Atabek-Yiğit et al, 2019;Durmuş, 2020;Egüz et al, 2017;Güdürü, 2021;Gürbüz, 2015;Gürbüz, 2022;Kan, 2009;Kayaalp et al, 2021;Konakay & Ergen, 2021;Uyanık, 2012;Uymaz, 2021;Palaz, 2017;Palaz & Akbaba, 2018;Sert, 2021;Şeyihoğlu et al, 2018;Yazıcı, 2013;Yiğit, 2019) and international literature (Alazzi, 2011;Bonnie et al, 2021;Bourn & Hunt, 2011;Canziani et al, 2021;Chou, 2020;Danielraja, 2019;Hashizaki & Kawaguchi, 2012;Mahler, 2020;Sabancı et al, C. (2017). Trumper, 2020Wongchantra & Nuangchalerm, 2011), focusing on global issues, revealed that studies nationally and internationally carried out by a wide sample range from primary and secondary school students, pre-service teachers, and social studies teachers to the Social Studies Curriculum taught in Turkey and abroad.…”
Section: Introductionmentioning
confidence: 99%
“…While using WAT, students are asked to write the word or group of words that come to their mind within the framework of a stimulus word in a very short time and then form a sentence (Çetinkaya, Sönmez & Topçam, 2020;Kostova & Radoynovska, 2010). When the relevant studies are examined, it is seen that the WAT is used to determine students' cognitive structures (Çetin & Timur, 2020;Ozer, 2020), conceptual changes (Hovardas & Korfiatis, 2006), and perceptions (Uluçınar Sağır, 2017). For example, WAT was used to determine the perceptions of students from different levels on the concepts of environmental pollution (Kalaycı, 2020), technology (Çetin & Timur, 2020), AIDS (Ekici & Kurt, 2014), social studies, and social sciences (Deveci, Köse & Bayır, 2014) and current, resistance and voltage concepts (Balbağ & Karademir, 2020).…”
Section: Introductionmentioning
confidence: 99%